A Comparative Study on Structural, Morphological, and Tensile Properties of Binary and Ternary Epoxy Resin-Based Polymer Nanocomposites - Dalia M. T. Mustafa; Sarkawt Rostam; Shujahadeen B. Aziz (Advances in Materials Science and Engineering, 2020)
In the present work, epoxy resin-based nanocomposites (NCPs) were fabricated with improved mechanical properties. The epoxy resin (EPR) was mixed with differing amounts of calcium titanate (CaTiO3) nanoparticles (NPs) and glass fiber. The results showed that the ternary system contained glass fiber exhibits low mechanical performance compared to binary [EPR:CaTiO3] system. The effect of fiber glass and NPs on the epoxy resin mechanical behavior was determined by conducting a tensile test for various specimen sets. From the mechanical characterizations, it was seen that there is a monotonic relationship between the NPs concentration and Young’s modulus. Additionally, NCPs samples were brittle in nature and the strain rate significantly decreased upon the addition of CaTiO3 concentration; while the tensile strength was increased. From the X-ray diffraction evaluation, it can be concluded that the addition of NPs have a great impact on the epoxy structure. Besides, the morphology appearance was in good agreement with structural and mechanical analysis.